Exploiting biogeochemical and spectroscopic techniques to assess the geochemical distribution and release dynamics of chromium and lead in a contaminated floodplain soil. (May 2016) - Rinklebe, Jörg; Shaheen, Sabry M.; Schröter, Felix; Rennert, Thilo
Abstract: Scanning electron microscopy (SEM) coupled with energy dispersive X-ray spectroscopy (EDX) combined with a seven steps sequential extraction technique were used to assess the geochemical distribution of chromium (Cr) and lead (Pb) in a contaminated floodplain soil. Total contents of Cr and Pb were 490.3 and 402.1 mg kg −1, respectively. The residual fraction was 59.5 and 56.3% of total Cr and Pb. The crystalline iron (Fe) oxide was the dominant non-residual fraction of Cr (35.9% of total Cr). Considerable amounts of Pb were found in the organic fraction (35.4%). Using 13 C nuclear magnetic resonance spectroscopy, the soil organic matter was identified as 48.9% aromatic carbon, which indicated that a certain portion of Pb and Cr might be associated with aromatic compounds. The SEM–EDX images demonstrate a concomitant occurrence of Pb, manganese (Mn), Fe, and aluminum (Al) as well as a coexistence of Cr and Fe. The release dynamics of dissolved Cr and Pb as affected by redox potential (EH ), pH, Fe, Mn, dissolved organic carbon, and sulfate was quantified using an automated biogeochemical microcosm apparatus. Soil pH decreased under oxic conditions. The release of Cr, Pb, Fe, and Mn increased under acidic oxic (pH = 3.7, EH = 521 mV) conditions due to the associated decrease of pH (7.1–3.7). The mobilization of Cr and Pb was affected by the Fe and Mn. In conclusion, our multi-technique approach identified the geochemical distribution of Cr and Pb and verified major factors that explain mobilization of Cr and Pb in floodplain soils. Highlights: New combination of biogeochemical and spectroscopic techniques. SEM–EDX images demonstrate concomitant occurrence of Pb, Mn, Fe, and Al. Coexistence of Cr and Fe was detected. Aromatic carbon identified by 13 C NMR spectroscopy dominated in this floodplain soil. Release of Cr, Pb, Fe, and Mn increased under acidic oxic conditions.